Helping Students to Get Better Grades in Mathematics at the Elementary Level - Naheed Khurshid, Hafiz Muhammad Ather khan, Hafiz Shehzad Ali (PJE, 2023)
The current study is conducted to explore the learning potential of students at the elementary level by using the scaffolding technique. The study aimed to measure the efficiency of the scaffolding teaching method provided to the students at the elementary level. The sample was selected from Gov. Girls Higher Secondary School Model Town A, Bahawalpur, Punjab, Pakistan.